2018
DOI: 10.2217/pmt-2017-0100
|View full text |Cite
|
Sign up to set email alerts
|

Meaningful Relief with Flurbiprofen 8.75 mg Spray in Patients with Sore Throat due to Upper Respiratory Tract Infection

Abstract: Flurbiprofen spray provides rapid, long-lasting and clinically meaningful relief from sore throat (ANZCTR: ACTRN12612000457842).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 10 publications
0
15
0
5
Order By: Relevance
“…The previous findings were confirmed with flurbiprofen spray in a study by de Looze et al 33 Patients were required to report at least 30 min of "at least moderate" sore throat relief on the STRRS for the relief to be regarded as "clinically meaningful". Significantly more patients using flurbiprofen spray reported at least 30 min of "at least moderate" relief than those using placebo during the 6 h after a single dose (55% vs 35%, respectively; OR: 2.31; 95% CI: 1.61, 3.62; p<0.0001), and this was achieved more quickly with flurbiprofen than placebo (HR: 1.96; 95% CI: 1.50, 2.57; p<0.0001); 150 min for flurbiprofen and not calculated for placebo due to less than 50% response.…”
Section: Meaningful Pain Reliefmentioning
confidence: 81%
See 4 more Smart Citations
“…The previous findings were confirmed with flurbiprofen spray in a study by de Looze et al 33 Patients were required to report at least 30 min of "at least moderate" sore throat relief on the STRRS for the relief to be regarded as "clinically meaningful". Significantly more patients using flurbiprofen spray reported at least 30 min of "at least moderate" relief than those using placebo during the 6 h after a single dose (55% vs 35%, respectively; OR: 2.31; 95% CI: 1.61, 3.62; p<0.0001), and this was achieved more quickly with flurbiprofen than placebo (HR: 1.96; 95% CI: 1.50, 2.57; p<0.0001); 150 min for flurbiprofen and not calculated for placebo due to less than 50% response.…”
Section: Meaningful Pain Reliefmentioning
confidence: 81%
“…Fourteen papers reported data on the effectiveness of singledose flurbiprofen 8.75 mg for relieving throat pain and soreness; 17,22,25,26,[28][29][30][31][32][33][34][35]37,38 11 included data for flurbiprofen lozenges, four for flurbiprofen spray and one for flurbiprofen microgranules. In a study by Schachtel et al, 17 single-dose flurbiprofen lozenge demonstrated a significantly greater reduction (85%) in sore throat pain intensity summed over the 2 h post-dose period (as measured on the STPIS) compared with placebo (p<0.001).…”
Section: Single Dosementioning
confidence: 99%
See 3 more Smart Citations